Equity and ethics in the Colombian tax collection: 1990-2010 - López Acero, Héctor Fernando; Chaparro Parra, Monica Shirley (Universidad Pedagógica y Tecnológica de Colombia, 2014)
This article aims to analyze the problematic of inequity in the Colombian tax system, particularly of the years 1990-2010, from ethical determinants inherited from the process of Spanish colonization. Although the Political Constitution expresses the principle of tax equity, the truth is that the tax reforms carried out since the 1990s have led to even more inequitable tax system. In response we could find out if the problem is more associated with disadvantages of administrative and technical type, or if the ethical complex typical of the Colombian significantly determines the development given to the fiscal issue.